To find the value of g(f(2)), we first need to find the value of f(2).
Substituting x = 2 into f(x) gives us:
f(2) = (2 - 2)/3 = 0/3 = 0
Now, we can substitute f(2) back into g(x):
g(f(2)) = g(0) = 3(0) + 2 = 0 + 2 = 2
Therefore, the value of g(f(2)) is 2.
Question
Let g left-parenthesis x right-parenthesis equals 3 x plus 2 and f left-parenthesis x right-parenthesis equals StartFraction x minus 2 over 3 EndFraction. Find the value.
g left-parenthesis f left-parenthesis 2 right-parenthesis right-parenthesis
(1 point)
Responses
1
1
0
0
2
2
one-third
1 answer